Study of responsibilities assignment methods in power quality (2012)
Abstract. The present document is a research report on the study of responsibilities assignment in power quality, theme proposed to be carried out as thesis for the degree of Doctor of Philosophy in Electrical Engineering at the National University of Colombia - Bogotá, the doctoral studies have been advised by the Professor Horacio Torres-Sánchez, who works at the National University of Colombia. A doctoral research project was proposed to guide the development of the doctorate. Besides a justification and a theoretical background about the analysis of responsibilities in power quality, the following preliminary objectives were proposed: _ To develop a methodology aimed to establish the responsibilities of different agents involved in a distribution network regarding power quality disturbances. _ Reviewing and studying of analysis tools useful to determine responsibilities of agents connected to a distribution system. Frequency domain, time domain and non-sinusoidal conditions aimed power theories are some of the analytic tools to be considered. _ Study, review and application of deterministic and random modeling and simulation techniques, in order to represent electric systems and power quality disturbances. Deterministic tools have been widely studied and additional efforts will be required just for specific cases. Random tools require the study of random variables, stochastic processes and Monte Carlo simulation techniques. _ Application of the methodology to real cases. This document reports the doctoral research, which was carried out in the National University of Colombia and the Ruhr University of Bochum - Germany. Along this document the main results achieved in the doctoral studies will be listed as well as the accomplishments of the preliminary proposed objectives. In order to introduce the reader to the theme investigated along the doctoral studies, a presentation of the Analysis of responsibilities is made in Chapter 1. In this chapter the conceptual realization of the analysis of responsibilities is described, such realization has been called the Responsibilities Assignment Problem RAP, once it is presented in terms of a problem to be solved, some details are necessary to orientate the finding of a suitable solution. The mentioned problem leads to new matters of discussion like: _ How should the responsibilities be assessed? _ How ought to be assigned the responsibilities? _ For the currently available methods to assess and assign responsibilities, in what manner must be carried out an evaluation to determine their usefulness and suitability? The precedent issues require a direction to facilitate and orientate the evaluation of the reviewed methods and to develop new ones, experimental cases and reference conditions will be proposed as basement for this purpose. Power Quality disturbances can be understood as any deviation from the conditions a customer or a utility needs to satisfy determined energy necessities, such disturbances have been listed and analyzed in technical standards. The analysis of deviations in the quality of the electric power demands the analysis of the electric power itself, an analysis leading to identify and quantify the disturbances in terms of power quantities and electric signals like voltages and currents. In the Chapter 2. A Review of power definitions will be done to provide a frame of reference to decompose power in parts related to the disturbances under consideration in the present thesis. As it was mentioned, reference conditions and experimental setups must be established to allow a comparative and critical revision of any RAP assessing method. Measurements and simulations have been carried out, a description of the setups, the measurements themselves and their usefulness is going to be presented. Simulations have been carried out as well, they shall be described in a similar way in Chapter 3. Once the conceptual foundation has been set already and the technical aspects and experimental cases have been presented too, a review of currently available methods is possible. Several methods shall be investigated, the Critical Impedance Method, the Multi- Point Method and the Harmonic Pollution Method among others, a critical assessment from the technical and conceptual perspective will be carried out, the assessment will yield desirable and undesirable characteristics of each method, which may be used to improve the methods or to develop new ones. This review can be found in Chapter 4. The doctoral research led to the development of a new method to assess responsibilities, the so called Method of Disturbances Interaction MDI, this method will be presented in Chapter 4 as well. Preliminary research results conducted to an improvement proposal for the Multi-Point Method, such improvement will be shown as well. Power quality disturbances evolve and change in time, their behavior cannot always be forecasted easily, the statistical analysis of disturbances is needed. A Statistical analysis procedure of the indicators to assess responsibilities in power quality is presented. The proposed method and the statistical analysis o_er the possibility of an integration of responsibilities assessment in the currently available standards, this part will be found in Chapter 5. Finally, the conclusions extracted from the thesis are presented along with a summary of the reviewed bibliography.